Knowledge support for environmental information on pharmaceuticals: experiences among Swedish Drug and Therapeutics Committees - Elkanah Linder; Björn Wettermark; Marie-Louise Ovesjö; Sofia Kälvemark Sporrong; Helena Ramström (BMC, 2023)
Abstract Background Two publicly available Swedish knowledge support systems, "Pharmaceuticals and Environment" on Janusinfo.se and Fass.se, provide environmental information on pharmaceuticals. Janusinfo is provided by the public healthcare system in Stockholm and Fass is provided by the pharmaceutical industry. The objectives of this study were to investigate the experiences among Swedish Drug and Therapeutics Committees (DTCs) with using the databases, retrieve development proposals for these, and investigate the DTCs' challenges with working with pharmaceuticals in the environment. Methods A cross-sectional survey with 21 questions, both closed and open-ended, was distributed electronically in March 2022 to Sweden's 21 DTCs. Descriptive statistics and inductive categorization were used for the analysis. Results A total of 132 respondents from 18 regions filled out the survey. The average regional response rate was 42%. The DTCs used the knowledge supports to consider environmental aspects of pharmaceuticals in their formularies and in education. Respondents were more familiar with Janusinfo compared to Fass but appreciated the availability of both. The DTCs especially valued the concrete proposals for certain active pharmaceutical ingredients on Janusinfo. Respondents requested that all medicinal products have environmental information on Fass. Challenges included lack of data, lack of transparency from the pharmaceutical industry and difficulties considering the environmental aspect of pharmaceuticals in their healthcare practice. Respondents wanted more knowledge, clear messages, and legislation to support their work to reduce the negative environmental impact of pharmaceuticals. Conclusions This study demonstrates that knowledge supports for environmental information on pharmaceuticals are valuable for the DTCs in Sweden, but the respondents experienced challenges in their work in this field. The study can provide insights to those in other countries interested in considering environmental aspects in their formulary decision-making.